2004
DOI: 10.1016/j.amjhyper.2004.03.666
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma lipid concentrations in early pregnancy and risk of preeclampsia*1

Abstract: Early pregnancy dyslipidemia is associated with an increased risk of preeclampsia. This association may be significant in understanding the pathologic processes of preeclampsia and may help in developing strategies for prevention or early diagnosis of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
153
5
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(182 citation statements)
references
References 28 publications
16
153
5
8
Order By: Relevance
“…Though in our own study, the mean value of HDL-C was about 30% higher in the third trimester of normal pregnancy over the nonpregnant women, but statistically the alteration was not significant (P>0.05). A tendency to lesser quantities of serum alpha lipoprotein fraction in women with toxaemia, particularly in the third trimester, was reported by many workers (6,7,9). In our study a significant decrease in HDL-C were observed in pre-eclamptic and eclamptic pregnant women.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Though in our own study, the mean value of HDL-C was about 30% higher in the third trimester of normal pregnancy over the nonpregnant women, but statistically the alteration was not significant (P>0.05). A tendency to lesser quantities of serum alpha lipoprotein fraction in women with toxaemia, particularly in the third trimester, was reported by many workers (6,7,9). In our study a significant decrease in HDL-C were observed in pre-eclamptic and eclamptic pregnant women.…”
Section: Resultssupporting
confidence: 78%
“…In present study there was a significant fall in LDL-C : HDL-C in normal pregnant women as compared to nonpregnant women. LDL-C : HDL-C however increased significantly in eclamptic women as compared to normal pregnant women (6,10). On the contrary, HDL-C : VLDL-C continued to fall in both preeclampsia and eclampsia.…”
Section: Resultsmentioning
confidence: 80%
“…Twenty‐seven studies reported on HDL levels,32, 37, 41, 44, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74 of which 24 studies could be included in a meta‐analysis 32, 37, 41, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72. HDL level was lower in pre‐eclampsia than in controls (mean difference −6.29 mmol/L; 95%CI −9.74−2.85; P  = 0.0003) with the strongest effect in subgroup analysis for severe pre‐eclampsia vs. controls ( Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the decreased catabolism of TG-rich lipoproteins by reduced placental uptake and the putative concomitant decrease of lipoprotein lipolysis results in the accumulation of TG-rich remnant lipoproteins in the maternal circulation. Remnant lipoproteins may induce platelet activation and endothelial dysfunction, thus leading to the major clinical symptoms of PE [7].…”
Section: Introductionmentioning
confidence: 99%